Discriminating the tectonic and non‐tectonic contributions in the ionospheric signature of the 2011, Mw7.1, dip‐slip Van earthquake, Eastern Turkey. Issue 11 (7th June 2013) - Rolland, Lucie M.; Vergnolle, Mathilde; Nocquet, Jean‐Mathieu; Sladen, Anthony; Dessa, Jean‐Xavier; Tavakoli, Farokh; Nankali, Hamid Reza; Cappa, Frédéric
<x xml:space="preserve">Abstract</x> [1] It has previously been suggested that ionospheric perturbations triggered by large dip‐slip earthquakes might offer additional source parameter information compared to the information gathered from land observations. Based on 3D modeling of GPS‐ and GLONASS‐derived total electron content signals recorded during the 2011 Van earthquake (thrust, intra‐plate event, Mw = 7.1, Turkey), we confirm that coseismic ionospheric signals do contain important information about the earthquake source, namely its slip mode. Moreover, we show that part of the ionospheric signal (initial polarity and amplitude distribution) is not related to the earthquake source, but is instead controlled by the geomagnetic field and the geometry of the Global Navigation Satellite System satellites constellation. Ignoring these non‐tectonic effects would lead to an incorrect description of the earthquake source. Thus, our work emphasizes the added caution that should be used when analyzing ionospheric signals for earthquake source studies.